Hubungan Lama Bekerja dengan Kejadian Computer Vision Syndrome pada Pekerja Pengguna Komputer - Rosiana Fajar Setiawan; Hilmi Zadah Faidullah; Razany Fauzia Alboneh (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The proliferation of computer use in the professional sphere has heightened the prevalence of occupational health issues, notably Computer Vision Syndrome (CVS). This condition, characterized by ocular and musculoskeletal discomfort, significantly impacts worker productivity and well-being. This study aimed to investigate the relationship between the duration of daily computer work and the incidence of CVS among office workers. A quantitative cross-sectional study was conducted at the Sleman District Health Office, involving 137 employees selected through a total sampling technique. Data were collected using the standardized Computer Vision Syndrome Questionnaire (CVS-Q), and the association between variables was analyzed using the Chi-Square test. The results revealed that 66.4% of participants experienced CVS symptoms. A statistically significant association was found between working for more than four hours per day on a computer and the incidence of CVS (p = 0.008). This finding underscores that prolonged daily computer use is a significant risk factor for developing CVS. The study concludes that limiting continuous screen time and implementing ergonomic interventions are crucial for mitigating the risk of CVS in the modern workplace.